2006
DOI: 10.1159/000093576
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Intima-Media Thickness in HIV-Infected Individuals: Relationship of Premature Atherosclerosis to Neuropsychological Deficits?

Abstract: Background: Intima-media thickness (IMT) measured by extracranial duplex sonography is a surrogate marker for atherosclerosis. It is well known that IMT is greater in HIV patients than in age-matched healthy controls due to HIV- induced endothelial damage and metabolic side-effects of antiretroviral therapy. However, it remains unclear whether atherosclerosis has an additional impact on cognitive function in HIV patients. Therefore, the objective of this study was to investigate the correlation between IMT and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Our results, together with observations from other populations [29][30][31][32][33]37], suggest the hypothesis that in the recent cART era the role of CV risk factors on the pathogenesis of cognitive impairment could be greater than that of traditional HIV-or cARTrelated variables, similar to findings obtained in HIVuninfected subjects. As a consequence, CV comorbidities should be adequately investigated at the time of neuropsychological examination, in order to better explore the aetiology of cognitive disorders in the HIV-positive population and to avoid classifying as affected by HAND those patients with prevalent vascular impairment.…”
Section: Discussionsupporting
confidence: 88%
“…Our results, together with observations from other populations [29][30][31][32][33]37], suggest the hypothesis that in the recent cART era the role of CV risk factors on the pathogenesis of cognitive impairment could be greater than that of traditional HIV-or cARTrelated variables, similar to findings obtained in HIVuninfected subjects. As a consequence, CV comorbidities should be adequately investigated at the time of neuropsychological examination, in order to better explore the aetiology of cognitive disorders in the HIV-positive population and to avoid classifying as affected by HAND those patients with prevalent vascular impairment.…”
Section: Discussionsupporting
confidence: 88%
“…Most studies showed a trend toward thicker CIMT among PI exposed patients, except four studies 12 21 24 32. The WMD for CIMT (fig 3) was not significantly different by PI exposure, WMD  = 0.02 mm (95% CI −0.01 to 0.06, p = 0.190); I2 = 93%, p<0.001).…”
Section: Resultsmentioning
confidence: 90%
“…Of 58 articles selected for detailed evaluation, 13 were excluded owing to missing data or comparison groups not relevant to our study question, 20 were duplicate data and 25 were included from the initial search 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32. After the addition of a study identified from the references of included articles a total of 26 articles were included 33.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations